Salmonella enterica Serovars Gallinarum and Pullorum Expressing Salmonella enterica Serovar Typhimurium Type 1 Fimbriae Exhibit Increased Invasiveness for Mammalian Cells - Wilson, Rebecca L. (American Society for Microbiology, 2000)
Salmonella enterica serovars Gallinarum and Pullorum are S. enterica biotypes that exhibit host specificity for poultry and aquatic birds and are not normally capable of causing disease in mammalian hosts. During their evolution toward host restriction serovars Gallinarum and Pullorum lost their ability to mediate mannose-sensitive hemagglutination (MSHA), a phenotype correlated with adherence to certain cell types. Because adherence is an essential requirement for invasion of cells by bacterial pathogens, we examined whether MHSA type 1 fimbriae would increase the ability of serovars Pullorum and Gallinarum to invade normally restrictive cells. Serovars Gallinarum and Pullorum expressing S. enterica serovar Typhimurium strain LT2 type 1 fimbriae exhibited a 10- to 20-fold increased ability to adhere to and a 20- to 60-fold increased invasion efficiency of the human epithelial HEp-2 cell line. Invasion was accompanied by extensive ruffling of the membranes of the HEp-2 cells. In a murine ligated ileal loop model, a 32% increase in the number of M-cell ruffles was seen when serovar Gallinarum expressed serovar Typhimurium type 1 fimbriae.